Editorial: the importance of utilising gastrointestinal ultrasound via transperineal approach in ulcerative colitis—an accurate early predictor of response to treatment. Issue 9 (16th April 2022) - Ardalan, Zaid S.; Friedman, Antony B.
LINKED CONTENT: This article is linked to Sagami et al papers. To view these articles, visit https://doi.org/10.1111/apt.16817 and https://doi.org/10.1111/apt.16895